Analysis of Students Ability on Creative Thinking Aspects in terms of Cognitive Style in Mathematics Learning with CORE Model Using Constructivism Approach - Konita, Mita; Sugiarto, Sugiarto; Rochmad, Rochmad (Unnes Journal of Mathematics Education, 2017)
Tujuan penelitian ini adalah untuk menguji hasil belajar kemampuan siswa pada aspek berpikir kreatif dengan model CORE menggunakan pendekatan konstruktivisme dapat mencapai ketuntasan klasikal; mengetahui rata-rata hasil belajar kemampuan siswa pada aspek berpikir kreatif dengan model CORE menggunakan pendekatan konstruktivisme lebih dari 75; mendeskripsikan gaya kognitif siswa dalam menjawab masalah dan kemampuan siswa pada aspek berpikir kreatif dalam pembelajaran matematika. Penelitian ini merupakan penelitian kombinasi (mixed methods). Populasi penelitian ini adalah siswa kelas X SMAN 6 Semarang. Hasil penelitian ini menunjukkan: (1) hasil belajar kemampuan siswa pada aspek berpikir kreatif dengan model CORE pendekatan konstruktivisme mencapai ketuntasan klasikal; (2) rata-rata hasil belajar kemampuan siswa pada aspek berpikir kreatif dengan model CORE pendekatan konstruktivisme lebih dari 75; (3) catatan waktu karakterikstik gaya kognitif reflektif terlambat namun frekuensi menjawab paling sedikit, sedangkan catatan waktu karakterikstik gaya kognitif implusif tercepat namun frekuensi menjawab paling banyak; (4) Kelompok siswa gaya kognitif reflektif memenuhi komponen berpikir kreatif yaitu fleksibilitas dan kebaruan serta kelompok siswa gaya kognitif implusif memenuhi komponen berpikir kreatif fleksibel dalam menjawab masalah. The purpose of this research is to determine learning outcomes in the aspect of creative thinking abilities with CORE model use a constructivist approach achieve mastery of classical, determine the mean result of learning on aspect of creative thinking abilities with CORE learning model use a constructivist approach is more than 75, to describe the characteristics of the cognitive styles of students in answering problems, and describe the creative thinking abilities based on cognitive style. This research is combined (mixed methods). The study population was class X SMAN 6 Semarang. The result of this research showed that : (1) learning outcomes in the aspect of creative thinking abilities with CORE learning model use a constructivist approach achieve mastery of classical; (2) the mean result of learning on aspect of creative thinking abilities with CORE learning model use a constructivist approach is more than 75; (3) the record time of reflective cognitive style characteristics is least so that it has less answering frequency, while the record time of implusive cognitive style characteristics is fast, it has more answering frequency; (4) the students’ group in implusive cognitive learning fulfill the creative thinking indicator of flexibility and novelty, while the students’ group in implusive cognitive learning fulfill the indicator of flexible creative thinking in overcoming the problems.